Numerical Simulation Study on the Descaling Mechanism of High-Pressure Swirling Jet - Zhong Yin; Chen Shu; Zhao Yuhong; Xue Yongzhi; Yao Lin (Shiyou jixie)
To further explore the active mechanism of swirling jet， a numerical model of swirling jet descaling was built， and its effectiveness was verified by comparing with experimental results. Then， the difference in flow field characteristics between swirling jet and conventional straight jet was compared， and the mechanism of overflow and erosion in the process of swirling jet descaling was revealed. Finally， the influence of pump pressure， target distance and jet angle on the descaling performance was analyzed. The study results show that the special nozzle structure determines the three-dimensional velocity distribution characteristics of the swirling jet. The swirling jet has a similar impact crushing capacity and a larger impact area as the conventional straight jet. An increase in pump pressure can significantly improve the descaling performance of the swirling jet， the target distance has an optimal value for affecting the descaling performance， and moderately increasing the jet angle can further promote the descaling effect. The study results provide reference for the optimal application of swirling jet in descaling operations.